2022
DOI: 10.26434/chemrxiv-2022-wwb35
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coupling the Batch Adsorption Enrichment using Ternary LDHs with Struvite Crystallization in a Fluidized Bed Reactor for High-efficiency Phosphorus Recovery from Wastewater

Abstract: Adsorption represents a well-documented, effective and reliable means for phosphorus (P) recovery from waste streams, and is often followed by chemical precipitation for attaining value-added fertilizers or feedstocks. To assess the feasibility of recovering P from water by combining batch adsorption enrichment with struvite crystallization, we prepared four ternary layered double hydroxides (LDHs) with P-preferring elements (i.e., zirconium (Zr) or lanthanum (La)) via a facile coprecipitation method, and then… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Rapid Adsorption/Desorption Test. Following the same desorption procedure described elsewhere, 11,37 our preliminary experiment has showed that a 0.1 M NaOH solution exhibited the maximum desorption efficiency and thus was employed as the eluent. Both simulated high-P wastewater and actual wastewater (i.e., the sludge dewatering liquid; see Table S1) were used as the effluent being tested.…”
Section: Phosphate Adsorption Experimentsmentioning
confidence: 99%
“…Rapid Adsorption/Desorption Test. Following the same desorption procedure described elsewhere, 11,37 our preliminary experiment has showed that a 0.1 M NaOH solution exhibited the maximum desorption efficiency and thus was employed as the eluent. Both simulated high-P wastewater and actual wastewater (i.e., the sludge dewatering liquid; see Table S1) were used as the effluent being tested.…”
Section: Phosphate Adsorption Experimentsmentioning
confidence: 99%